Multi Cumulative Prospect Theory and the Demand for Cliquet‐Style Guarantees. Issue 4 (10th January 2017) - Ruß, Jochen; Schelling, Stefan
Abstract: Expected Utility Theory (EUT) and Cumulative Prospect Theory (CPT) face problems explaining preferences of long‐term investors. Previous research motivates that the subjective utility of a long‐term investment also depends on interim value changes. Therefore, we propose an approach that we call Multi Cumulative Prospect Theory. It is based on CPT and considers annual changes in the contract values. As a first application, we can show that in contrast to EUT and CPT, this approach is able to explain the demand for guaranteed products with lock‐in features, which in this framework generate a higher subjective utility than products without or with simpler guarantees.